The role of school factors in the demand of middle school students for private lessons under the reforms of the second generation :: An empirical study - GUESMI, Sonia (Journal of Human Sciences, 2020)
This work aims to reveal the school factors leading to the participation of middle school students in private lessons, by focusing on two factors: School curricula and teaching methods, and to achieve the proposed hypotheses the study used the descriptive method using the questionnaire applied to a sample Consisting of (40) students who take private lessons in different subjects.The study concluded that the school curricula have a role in pushing middle school students to take private lessons, because they are not in line with their aspirations and cognitive abilities, as the study also found that teaching methods used by teachers also have a role in pushing pupils into private lessons.